OpenGeoSys Tutorial Computational Hydrology III: OGS#IPhreeqc Coupled Reactive Transport Modeling - Jang, Eunseon (SpringerBriefs in Earth System Sciences,, 2018)
This tutorial provides the application of the coupling interface OGS#IPhreeqc (open-source scientific software) to model reactive mass transport processes in environmental subsurface systems. It contains general information regarding reactive transport modeling and step-by-step model set-up with OGS#IPhreeqc and related components such as GINA and ParaView. Benchmark examples (1D to 2D) are presented in detail. The book is intended primarily for graduate students and applied scientists who deal with reactive transport modeling. It also gives valuable information to the professional geoscientists wishing to advance their knowledge in numerical simulation, with the focus on the fate and transport of nitrate. It is the third volume in a series that represents the further application of computational modeling in hydrological science.